2021
DOI: 10.1183/23120541.00420-2021
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cough in Germany: results from a general-population survey

Abstract: BackgroundChronic cough (CC) which is defined≥8 weeks is a common condition in clinical practice. However, estimates of prevalence and associated comorbidities in German adults and key subgroups of age and gender are lacking.MethodsCross-sectional study based on a representative panel of 15,020 adult subjects of the general population who completed the German National Health and Wellness Survey, reporting chronic cough and questions about comorbidities. Lifetime and 12-month prevalence are presented as unweigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 38 publications
4
17
3
Order By: Relevance
“…The main findings of this study are: (1) the prevalence of chronic cough in a large (n = 10,057), adult general population cohort in Austria was 9%, with no sex differences but an increase with age; (2) 85% of participants with chronic cough had at least one condition associated with chronic cough, and (3) current (but not former) smoking, low socioeconomic status, obesity and obstructive sleep apnea were factors associated with chronic cough, with current smoking (over 20 pack years) being the greatest factor. Finally, 15% of participants with The prevalence of chronic cough in our study (9%) is consistent with previous studies, in which prevalence ranged between 4% and 13% [5,[9][10][11][12][13][14][15]. We did not find any impact of sex on chronic cough prevalence, in contrast with previous reports where there was a higher prevalence of chronic cough in females attending cough clinics [16,17], although our data agree with several population based studies in the UK [18],…”
Section: Discussionsupporting
confidence: 92%
“…The main findings of this study are: (1) the prevalence of chronic cough in a large (n = 10,057), adult general population cohort in Austria was 9%, with no sex differences but an increase with age; (2) 85% of participants with chronic cough had at least one condition associated with chronic cough, and (3) current (but not former) smoking, low socioeconomic status, obesity and obstructive sleep apnea were factors associated with chronic cough, with current smoking (over 20 pack years) being the greatest factor. Finally, 15% of participants with The prevalence of chronic cough in our study (9%) is consistent with previous studies, in which prevalence ranged between 4% and 13% [5,[9][10][11][12][13][14][15]. We did not find any impact of sex on chronic cough prevalence, in contrast with previous reports where there was a higher prevalence of chronic cough in females attending cough clinics [16,17], although our data agree with several population based studies in the UK [18],…”
Section: Discussionsupporting
confidence: 92%
“…In a study of young adults in Italy, socioeconomic status according to occupation had an effect on the prevalence of chronic cough [35]. In a German study, neither income nor education level affected the prevalence of chronic cough; however, as in our study, employment status was associated with chronic cough [32]. However, blue-collar occupation or high household income had no signi cant effect on chronic cough in another study [30].…”
Section: Discussioncontrasting
confidence: 47%
“…Previous studies have shown that the prevalence of chronic cough is signi cantly increased in the elderly [29,[31][32][33]. In a study on the general Korean population, age over 65 years was also reported as one of the risk factors for chronic cough [30].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have shown that the prevalence of chronic cough is significantly increased in the elderly [29,[31][32][33]. In a study on the general Korean population, age over 65 years was also reported as one of the risk factors for chronic cough [30].…”
Section: Discussionmentioning
confidence: 96%